2022
DOI: 10.3390/cells11121906
|View full text |Cite
|
Sign up to set email alerts
|

In Search of the Holy Grail: Toward a Unified Hypothesis on Mitochondrial Dysfunction in Age-Related Diseases

Abstract: Cardiolipin (CL) is a mitochondrial signature phospholipid that plays a pivotal role in mitochondrial dynamics, membrane structure, oxidative phosphorylation, mtDNA bioenergetics, and mitophagy. The depletion or abnormal acyl composition of CL causes mitochondrial dysfunction, which is implicated in the pathogenesis of aging and age-related disorders. However, the molecular mechanisms by which mitochondrial dysfunction causes age-related diseases remain poorly understood. Recent development in the field has id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 104 publications
(169 reference statements)
0
14
0
Order By: Relevance
“…Instead, CL remodeling by ALCAT1 results in the enrichment of docosahexaenoic acid (DHA) and arachidonic acids, leading to CL having a high sensitivity to oxidants [ 33 ]. As a consequence, increased expression of ALCAT1 may directly lead to oxidative stress and mitochondrial dysfunction in cells [ 33 , 39 , 40 , 41 , 42 ]. Actually, the diversity in the acyl chain composition in different cells and tissues is regulated by differences in CL synthesis, catabolism, and remodeling, and the acyl chain composition has been shown to play an important role in regulating inner membrane fluidity, structure, osmotic stability, and protein properties [ 43 , 44 , 45 ].…”
Section: CL Biosynthesis and Remodelingmentioning
confidence: 99%
“…Instead, CL remodeling by ALCAT1 results in the enrichment of docosahexaenoic acid (DHA) and arachidonic acids, leading to CL having a high sensitivity to oxidants [ 33 ]. As a consequence, increased expression of ALCAT1 may directly lead to oxidative stress and mitochondrial dysfunction in cells [ 33 , 39 , 40 , 41 , 42 ]. Actually, the diversity in the acyl chain composition in different cells and tissues is regulated by differences in CL synthesis, catabolism, and remodeling, and the acyl chain composition has been shown to play an important role in regulating inner membrane fluidity, structure, osmotic stability, and protein properties [ 43 , 44 , 45 ].…”
Section: CL Biosynthesis and Remodelingmentioning
confidence: 99%
“…We would also like to highlight our identification of the MICOS complex protein MIC19 as a target for VAP-B- and SPHKAP-dependent PKA phosphorylation downstream of GLP-1R activity, as this protein is not only a key member of the mitochondrial cristae junctions, and therefore responsible for the organisation of mitochondrial inner and outer membrane contacts and overall architecture of respiratory complexes as well as the mitochondrial proton pump, but it has also been recently unveiled to play a prominent role in the formation of ERMCSs, where it enables the transfer of lipid precursors for the biosynthesis of the key mitochondrial lipid cardiolipin 57 , therefore connecting mitochondrial cristae organisation with the generation of cristae membrane curvature and the control of mitochondrial function afforded by cardiolipin 39 . We therefore hypothesise that GLP-1R-dependent phosphorylation of MIC19 via the VAP-B – SPHKAP – PKA pathway might not only indicate a direct role for the receptor in controlling cristae architecture and mitochondrial turnover, but also in the regulation of lipid precursor transfer across ERMCSs to meet the β-cell requirement for cardiolipin synthesis to sustain mitochondrial turnover and renewal at times of high metabolic demand, particularly as alterations in cardiolipin profiles have been reported in several diseases where GLP-1RAs play beneficial roles, such as Alzheimer’s, Parkinson’s, obesity, and T2D 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the α-synuclein accumulation in the brainstem is also a mechanism contributing to the pathogenesis of iRBD. Melatonin can reduce the aggregation of α-synuclein and exerts neuroprotective effects by scavenging free radicals ( 84 , 85 ), stimulating glutathione synthesis ( 86 , 87 ), enhancing antioxidant enzyme synthesis, and inhibiting the production of pro-oxidant enzymes ( 88 , 89 ), thus alleviating α-synuclein’s mitochondrial toxicity ( 90 , 91 ). Thirdly, studies have reported that inflammation plays a role in the pathogenesis of iRBD ( 92 , 93 ).…”
Section: Discussionmentioning
confidence: 99%